1994
DOI: 10.1143/jjap.33.270
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of CeO2 Films on Si(111) by Sputtering

Abstract: CeO2 films were epitaxially grown on Si(111) substrates by reactive sputtering following the single-crystal CeO2 seed layer formation by oxygen-reactive solid-phase epitaxy. Formation of metallic Ce layers and oxidation of the layers prior to reactive sputtering was found to be the key process for epitaxial growth of CeO2 on Si substrates. An Auger electron spectroscopy depth profiling analysis showed that the Ce–Si interlayer was formed after the Ce metal deposition. Reflection high-energy electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…1). This result is in agreement with many reports dealing with the deposition of CeO 2 on a (111) Si substrate, realized by e-beam evaporation, [1] sputtering, [5] using low-energy dual-beam deposition technology [6] or laser ablation. [7] CeO 2 powder used to fabricate the targets and CeO 2 targets were characterized by RS (Fig.…”
Section: Resultssupporting
confidence: 93%
“…1). This result is in agreement with many reports dealing with the deposition of CeO 2 on a (111) Si substrate, realized by e-beam evaporation, [1] sputtering, [5] using low-energy dual-beam deposition technology [6] or laser ablation. [7] CeO 2 powder used to fabricate the targets and CeO 2 targets were characterized by RS (Fig.…”
Section: Resultssupporting
confidence: 93%
“…This attractive set of properties has the potential to lead to a fully functional silicon heterojunction technology. A significant amount of work has been done examining the growth and characterization of CeO 2 crystals on Si, [1][2][3][4][5] and the growth of single crystal Si on to CeO 2 /Si heterostructures 6 has been recently reported. Based on these promising results, a silicon resonant tunneling diode, an improved silicon-on-insulator technology, and stacked silicon electronics have all been proposed.…”
mentioning
confidence: 99%
“…Epitaxial growth of CeO 2 layers was accompanied by simultaneous oxidation of the underlying Ce-silicide layer. The two-step growth method similar to this study has already been reported in growing epitaxial CeO 2 (1 1 1)/Si(1 1 1) structures [6], but our method is different from theirs in the points of the use of a very thin metallic Ce layer and not having an intentional oxidation process before CeO 2 deposition but having a silicidation process before CeO 2 layer deposition.…”
Section: Two-step Growthmentioning
confidence: 93%
“…For applications to silicon technology, epitaxial growth of CeO 2 thin films on Si substrates has been studied, where a great deal of effort has been devoted to make use of close epitaxial relations of CeO 2 with silicon: both materials have cubic symmetry and a lattice mismatch parameter between them is a very small value of 0.35%. Epitaxial growth of CeO 2 layers on Si substrates has been studied for the application to microelectronics [1][2][3][4][5][6][7][8][9]. Although CeO 2 (1 1 1) layers grow on Si(1 1 1) substrates at very low temperatures, such as room temperature with excellent crystallinity [1][2][3][4][5][6][7], epitaxial growth on Si(1 0 0) substrates requires higher growth temperature and has strong tendency to grow with (1 1 0) orientation [1,8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation